Effect of p27Kip1 Inhibition on Proliferation of Bovine Corneal Endothelial Cells by RNA Interference - 黄渝侃 张明昌 王勇 范可顺 张光红 周莉 (Journal of Huazhong University of Science and Technology. Medical sciences, 2008)
Three plasmids （pGenesil-P1, pGenesil-P2, pGenesil-P3） with different p27Kip1-shRNA sequences were designed and synthesized. Their effects on the proliferation of bovine corneal endothelial cells （bCEC） were investigated. Plasmid expressing irrelevant shRNA with a random combination was used as negative control （pGenesil-HK）. The recombination of four plamids was confirmed by restrictive enzyme digestion and sequence analysis. The expression of mRNA and protein of p27Kip1 was detected by RT-PCR and Western blotting after stable transfection. The expressions of p27Kip1 mRNA and p27Kip1 protein of pGenesil-P1 group, pGenesil-P2 group and pGenesil-P3 group were all lower than those in the pGenesil-HK group and the blank group （non-transfected group）, pGenesil-P3 had the strongest inhibitory effect and was selected for the next steps. The proliferation rates of the pGenesil-P3 group, the pGenesil-HK group and the blank group were assessed by MTT. The influence of shRNA-p27Kip1 on bCEC cell cycle was detected by flow cytometry （FCM）. Compared with the control groups, the proliferation rate of the pGenesil-P3 group was increased significantly, and the ratio of S-phase also increased. It is concluded that shRNA-p27Kip1 could down-regulate the expression of p27Kip1 effectively and increase the proliferation of bCEC. RNA interference （RNAi） may be an effective means to promote the proliferation of CEC.